2022
DOI: 10.1242/jcs.259456
|View full text |Cite
|
Sign up to set email alerts
|

The histone variant macroH2A1.1 regulates RNA polymerase II-paused genes within defined chromatin interaction landscapes

Abstract: The histone variant macroH2A1.1 plays a role in cancer development and metastasis. To determine the underlying molecular mechanisms, we mapped the genome-wide localization of endogenous macroH2A1.1 in the human breast cancer cell line MDA-MB 231. We demonstrate that macroH2A1.1 specifically binds to active promoters and enhancers in addition to facultative heterochromatin. Selective knock-down of macroH2A1.1 deregulates expression of hundreds of highly active genes. Depending on the chromatin landscape, macroH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 90 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…While our epigenomic analysis points out the enrichment of both mH2A1 and mH2A2 at mBE, our data suggest a specific role for mH2A2 as a repressor, consistent with its role as a barrier to iPS reprogramming 23 . Other studies have shown mH2A1 isoforms to be implicated in regulation of enhancers but were limited to one cellular model or a particular mH2A isoform, e.g., mH2A1.2 in skeletal muscle C2C12 56 and mH2A1.1 in MDA-MB-231 cells 57 . Even if our focus was on the functional role of mH2A2 at enhancers, the enrichment of both variants is important to define mBEs and the effect we observed from the dKO MaSC suggests that mBEs function as a fine-tuning mechanism rather than indispensable regulators of normal development.…”
Section: Discussionmentioning
confidence: 99%
“…While our epigenomic analysis points out the enrichment of both mH2A1 and mH2A2 at mBE, our data suggest a specific role for mH2A2 as a repressor, consistent with its role as a barrier to iPS reprogramming 23 . Other studies have shown mH2A1 isoforms to be implicated in regulation of enhancers but were limited to one cellular model or a particular mH2A isoform, e.g., mH2A1.2 in skeletal muscle C2C12 56 and mH2A1.1 in MDA-MB-231 cells 57 . Even if our focus was on the functional role of mH2A2 at enhancers, the enrichment of both variants is important to define mBEs and the effect we observed from the dKO MaSC suggests that mBEs function as a fine-tuning mechanism rather than indispensable regulators of normal development.…”
Section: Discussionmentioning
confidence: 99%
“…In a limited case series of morbidly obese patients, the expression of macroH2A1.1 was specifically and massively increased in the adipose tissue, correlating with the BMI 27 . The histone variant macroH2A1.1 contains a macrodomain capable of binding NAD + -derived metabolites, which is not present in macroH2A1.2, which is thought to mediate some of its specific cellular functions such as gene expression and modulation of mitochondrial respiration 28 , 29 . We recently generated a mouse model where the histone variant isoform macroH2A1.1, but not macroH2A1.2, was depleted in the whole body 30 .…”
Section: Introductionmentioning
confidence: 99%
“…mH2A1 is enriched at heterochromatin domains on the inactive X chromosome (Xi) [7,8] or on autosomes. Concerning the latter, mH2A1 forms large domains at facultative heterochromatin [9][10][11], to a lesser extent, at constitutive heterochromatin marked with the histone mark H3K9me3 [12], and at silent ribosomal DNA segments (rDNA) [13]. Moreover, in senescent cells, this histone variant is incorporated into Senescence-Associated Heterochromatin Foci (SAHFs) [14], which are composed of both heterochromatin types and pericentromeric DNA regions [15,16].…”
Section: Introductionmentioning
confidence: 99%